A systematic literature review of the impact of gamification instruction on students’ problem-solving skills - Feng, Jiyuan; Tan, Wee Hoe; Yu, Bin (Institute of Advanced Engineering and Science, 2024)
Gamification is a popular approach to teaching and learning in education in recent years, it provides the flexible integration of various game elements into educational activities to achieve instructional objectives. This approach has the potential to enhance student skills through interactive communication and motivation and has, sparked interest and discussion in many fields, including education. This review assesses the impact of gamification on student skills in terms of teaching methods, learning outcomes, and challenges faced. The study analyzed 21 research articles from three databases, Web of Science (WoS), Scopus, and ERIC, up to November 2023. The findings were grouped into three main themes: teaching implementation and methods (8 articles), learning outcomes and skill development (8 articles), and challenges and improvement strategies (5 articles). The findings suggest that although gamification has gained more results in the field of education, especially in terms of improving students’ skills and teaching effectiveness, there are shortcomings in integrating it with professional education. This review mainly highlights the impact of gamification in the development of students’ skills while considering gamification in conjunction with other aspects of education to illustrate the need for ongoing research and further exploration in the field of education.